The Impact of Guided Inquiry Model Integrated with Peer Instruction towards Science Process Skill and Physics Learning Achievement - Hestingtyas Yuli Pratiwi; Muhammad Nur Hudha; Mathilda Asri; Nur Jahan Ahmad (Universitas PGRI Kanjuruhan Malang, 2019)
The aim of the research is to find out the difference in science process skill and learning achievement between students who are taught using guided inquiry model integrated with peer instruction and conventional method in VII students in one of the junior high schools in Malang. The method used is quasy-experimental with only post-test group design. The sample was selected using purposive sampling technique, from the 10 population of VII grade students; the researchers selected two classes which were considered to have the same initial skill with total 32 students in each class to be the experimental class and the control class. Instruments used were the observation sheets to measure the science process skill and the test of multiple choices to measure the learning achievement. The researchers gained average score of 81 for science process skill in experimental class and 58 in control class, while the average score of 77.8 for learning achievement in experimental class and 71.3 in control class as the result of the data analysis. The hypothesis test used T-test, that was the independent sample T-test on Microsoft excel by looking up the score of Ttable on the rate of sig 0.05 for the science process skill and it gained Tcount > Ttable (18.846 > 1.669), while the learning process gained Tcount > Ttable (8.465 > 1.669). It was concluded that the guided inquiry model integrated with peer instruction can improve student’s science process skill and learning achievement compared to conventional method